(untitled) (International Journal of Child Health and Nutrition, 2013)
The study aims to assess the relation between breastfeeding duration and age at menarche. Analysis was based on a cross sectional study on adolescent girls in the age group 10 – 15 years. The main outcome was self-reported age at menarche. Pearson’s correlation was used to investigate the relation between duration of exclusive and any breastfeeding with age at menarche with adjustment sequentially for specific sets of known socioeconomic, maternal, and genetic, confounders [1]. Menarche is a critical biomarker in the reproductive life of females [2]. It serves as an intermediate health outcome that affects women’s wellbeing at later stages of life [3]. There appears to be trend for decreasing age at menarche worldwide. There are contradictory reports of lowering age at menarche due to increasing BMI in the population [4]. The tempto, level of growth and maturation during adolescence may have important implication to future adult health. The purpose of the study was to examine mode of feeding in infancy and its effect on BMI and age at menarche [5]. 700 girls, 10-15 years were selected by multistage random sampling procedure. Age of the girls, Socioeconomic Status, BMI, menstrual status and mode of feeding in infancy were identified by questionnaire. Quetelet Index (wt/h2) was used to identify the BMI. B. G. Prasad method of social classification was used to grade the Socio economic Status [6]. Mean age at menarche was found to be 12.36±1.15 years. It was observed that mode of feeding infancy was significantly correlated (P< 0.01) with the age at menarche, Socioeconomic Status and educational qualification of mothers. However, the study suggested that girls who were formula fed deposit more body fat and were overweight.